"I'll Fly Away": A Genealogy of Maternal Love and Leave-taking - Silverwood, Rozanne (2018)
The over-medicalization of dying often renders family conversations about what constitutes a "good death" fraught with fear and denial. This thesis examines one family's breach of that forbidden storytelling terrain in a search for meaning and belonging in the face of death and dying. Incorporating Charlotte Linde's theories of "narrative acquisition" and Cree historian Winona Wheeler's indigenous perspectives on generational memory and kinship/relations, this intergenerational project veers from distinctly Western perspectives of interviewer/interviewee power relationships to consider familial "obligations" as essential to the preservation of ancestral knowledge about death and dying. To make meaning from deeply personal narratives of loss, the project's narrators rely upon a shared emotional language that they call "the maternal dialogic." The results evidence the valuable role that oral history serves as family members negotiate the end-of-life needs of loved ones while also navigating the varied emotions arising from bereavement and the reality of our own inevitable ends. Maternal Dialogic, Family Narrative